Satisfacción y calidad de enseñanza en modalidad remota en estudiantes de la escuela profesional de educación inicial de la facultad de ciencias de la educación y humanidades, Iquitos 2020 - Zapata Tapullima, Manuela Iris (2023)
The research results are presented to determine the relationship between the level of satisfaction and the quality of remote teaching in students at the Professional School of Initial Education of the Faculty of Education and Humanities Sciences in Iquitos during the year 20202. The population and sample consisted of 348 students. The cross-sectional design of field and bivariate was considered to carry out the study. Two questionnaires were developed for data collection, which were subject to validation by experts using the survey as a technique. The research is relational. In addition, it was found that the relationship between the variable satisfaction and the quality of remote teaching is very high positive; that is, the higher the student’s satisfaction, the higher the quality of remote teaching. It is also inferred that there is a statistically significant relationship between student satisfaction variable and remote teaching quality because rho=0.980**; Sig. < 0.000., values that allow demonstrating the research hypothesis: “There is a significant relationship between the level of satisfaction and the quality of remote teaching in students of the Professional School of Initial Education of the Faculty of Education and Humanities Sciences, Iquitos, 2020”